Correction to "New experimental data and reference models for the viscosity and density of squalane" - Schmidt,KAG; Pagnutti,D; Curran,MD; Singh,A; Trusler,JPM; Maitland,GC; McBride-Wright,M (Journal of Chemical and Engineering Data, 2016)
Empirical models for the density and the viscosity of squalane (C30H62; 2,6,10,15,19,23-hexamethyltetracosane) have been developed based on an exhaustive review of the data available in the literature and new experimental density and viscosity measurements carried out as a part of this work. The literature review shows there is a substantial lack of density and viscosity data at high temperature (373 to 473) K and high pressure conditions (pressures up to 200 MPa). These gaps were addressed with new experimental measurements carried out at temperatures of (338 to 473) K and at pressures of (1 to 202.1) MPa. The new data were utilized in the model development to improve the density and viscosity calculation of squalane at all conditions including high temperatures and high pressures. The model presented in this work reproduces the best squalane density and viscosity data available based on a new combined outlier and regression algorithm. The combination of the empirical models and the regression approach resulted in models which could reproduce the experimental density data with average absolute percent deviation of 0.04 %, bias of 0.000 %, standard deviation of 0.05 %, and maximum absolute percent deviation of 0.14 % and reproduce the experimental viscosity data with average absolute percent deviation of 1.4 %, bias of 0.02 %, standard deviation of 1.8 %, and maximum absolute percent deviation of 4.9 % over a wide range of temperatures and pressures. On the basis of the data set used in the model regression (without outliers), the density model is limited to the pressure and temperature ranges of (0.1 to 202.1) MPa and (273 to 525) K, whereas the viscosity model is limited to the pressure and temperature ranges of (0.1 to 467.0) MPa and (273 to 473) K. These models can be used to calibrate laboratory densitometers and viscometers at relevant high-temperature, high-pressure conditions.